Systematic search for single nucleotide polymorphisms in the FOXC2 gene: The absence of evidence for the association of three frequent single nucleotide polymorphisms and four common haplotypes with Japanese type 2 diabetes - OSAWA, Haruluko; ONUMA, Hiroshi; MURAKAMI, Akiko; OCHI, Masaaki; NISHIMIYA, Tatsuya; KATO, Kenichi; SHIMIZU, Ikki; FUJII, Yasuhisa; OHASHI, Jun; MAKINO, Hideichi (Diabetes (New York, N.Y.), 2003)
FOXC2, a forkhead/winged helix transcription factor, represents a promising candidate gene for type 2 diabetes since transgenic mice that specifically overexpress this gene in adipocytes are lean and insulin sensitive. To determine whether there are single nucleotide polymorphisms (SNPs) in this gene that are associated with type 2 diabetes, sequences of the coding and approximately 1 kb of 5' flanking regions in 24 Japanese type 2 diabetic subjects were initially analyzed using PCR direct sequencing, and the regions containing the identified polymorphisms were then examined. In 200 control subjects, three frequent SNPs were found (g. -512C>T [32.3%] and -350G>T [13.0%] in the 5' flanking region and +1548C>T [10.0%] in the 3' flanking region). Linkage disequilibria were found between all three pairs of these SNPs. Of the eight possible haplotypes defined by these SNPs, only four were found. When the frequencies of these SNPs and the four common haplotypes between 195 type 2 diabetic and 200 control subjects were compared, no association was evident. The +898C>T (Pro300Ser), +907C>A (Leu303Met), 1167_1169delCCA (389delHis), and +1251C>A (Ala417Ala) identified in the coding region were rare, although +907C>A could be higher in type 2 diabetic subjects (1.5%) than in control subjects (0.3%). Thus, the SNPs identified in the FOXC2 gene are unlikely to have major effects on susceptibility to Japanese type 2 diabetes.